THE STANCE OF CRITICAL RESEARCH PERIODICAL IN MEDICAL JOURNALISM - Saeeda Baig (ziauddin University, 2024)
Medical journalism, a world of aggressively competitive periodicals, may not always be based of valid, reliable or accurate information. A large productivity and wide array of medical research literature makes even the most virtuous scientists unable to gauge and assess through all of them hence a critical and systematic analysis is required to endorse its reliability for best evidence-based practices, which no doubt is the major backbone of medicine. By introducing critical appraisal, we can help the clinicians to avoid reading flawed literature and prevent the incorporation of biased or untrustworthy information into their practice. The world is more than ever competitive now (more than 12,000 new articles added every week to the MEDLINE database) and to stay updated with new ideas, most recent developments, latest results, functional and valuable technical progress with robust scientific evidence is becoming vital.